Promoting Labor Market Participation and Social Inclusion in Europe and Central Asia's Poorest Countries - World Bank (Washington, DC, 2015)
This report, funded by the Trust Fund for Environmentally and Socially Sustainable Development (TFESSD), seeks to identify labor market inequalities in the ten countries outlined above, to relate these inequalities to other forms of social exclusion, and to propose areas for policy action aimed at boosting labor market participation. The remainder of the report is structured as follows. Chapter two describes the role that jobs play in fostering good living standards, productivity and social cohesion, and contextualizes the discussion on jobs and participation in the ten countries. Chapter three zooms in, highlighting inequalities in labor force participation across demographic groups. Chapter four shifts the focus to the factors explaining unequal labor force participation across groups, and discusses a policy agenda for these ten countries, drawing on experiences from the rest of the world. Chapter five concludes.